Studi Literatur Pengaruh Sesar Geologi terhadap Kestabilan Lereng Tambang Batubara di Indonesia - Ridho Rizky Amanda (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The stability of slopes in open-pit coal mining in Indonesia is significantly influenced by geological faults, which are a major factor causing slope failures. This study aims to examine the impact of faults on slope stability by conducting a systematic literature review of 25 scientific publications from 2018 to 2025. The results indicate that faults and fault zones consistently reduce rock mass integrity through several mechanisms, including stress concentration in weak zones, the formation of preferential sliding surfaces, amplification of hydro-mechanical effects from groundwater and rainfall, and the reduction of rock strength parameters. Case studies in Kalimantan and Sumatra confirm these mechanisms with slope failures aligning with fault orientations. Kinematic and numerical analyses using the Limit Equilibrium Method (LEM), Finite Element Method (FEM), and Distinct Element Method (DEM) show a reduction in the safety factor (SF) by up to 36% on slopes affected by faults. Practical recommendations include continuous monitoring using Slope Stability Radar (SSR), optimization of slope geometry with angles < 18° in fault zones, groundwater control, reinforcement with anchors and bolting, and UAV-based discontinuity mapping for hazard zoning. This study concludes that managing slopes in fault zones requires an integrated approach combining detailed geological investigation, multi-method numerical analysis, real-time monitoring, and specific mitigation design.